Currency Crises and Monetary Policy in an Economy with Credit Constraints - Philippe Aghion; Philippe Bacchetta; Abhijit Banerjee (Swiss National Bank, Study Center Gerzensee, 2000)
This paper presents a simple model of currency crises which is driven by the interplay between the credit constraints of private domestic firms and the existence of nominal price rigidities. The possibility of multiple equilibria, including a "currency crisis" equilibrium with low output and a depreciated domestic currency, results from the following mechanism: if nominal prices are "sticky", a currency depreciation leads to an increase in the foreign cur- rency debt repayment obligations of firms, and thus to a fall in their profits; this reduces firms' borrowing capacity and therefore investment and output in a credit-constrained economy, which in turn reduces the demand for the domestic currency and leads to a depreciation. We examine the impact of various shocks, including productivity, fiscal, or expectiational shocks. We then analyze the optimal monetary policy to prevent or solve currency crises. We also argue that currency crises can occur both under fixed and flexible exchange rate regimes as the primary source of crises is the deteriorating balance sheet of private firms.
Keywords: 330; Geldpolitik; Währungskrise; Liquiditätsbeschränkung; Wirtschaftsmodell; Theorie